Novel Self‐Report Tool for Cardiovascular Risk Assessment - Hend Mansoor; Ara Jo; V. Madsen Beau De Rochars; Carl J. Pepine; Arch G. Mainous (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background The currently used atherosclerotic cardiovascular disease risk calculator relies on several measured variables and does not incorporate some well‐established risk factors such as family history of premature myocardial infarction and other nontraditional risk factors. Our study aimed to develop and validate a simple risk score to predict 10‐year risk of incident cardiovascular events using patient‐reported information. Methods and Results Using data from the Atherosclerosis Risk in Communities cohort, we identified adults with no previous history of cardiovascular disease and randomly divided the cohort into “development” (70%) and “validation” (30%) subgroups. Adjusted Cox regression modeling was used to develop a prediction model. The predictive performance of the new risk score was compared with the score derived from the atherosclerotic cardiovascular disease risk calculator. A total of 9285 individuals met the inclusion criteria. During follow‐up (median 8.93 years), a total of 694 (7.47%) incident cardiovascular events occurred. The following 6 factors were included: male sex, age, current smoking, diabetes mellitus, hypertension, and family history of premature myocardial infarction. The C‐statistic was 0.72 in the validation cohort with good calibration. The area under the curve for the simple risk score was comparable to the atherosclerotic cardiovascular disease risk score. Conclusions The novel simple risk score is an easy‐to‐use tool to predict cardiovascular events in adults from self‐reported information without need for laboratory or physical examination data. This risk score included 6‐items and had comparable predictive performance to the guideline recommended atherosclerotic cardiovascular disease risk score but relies solely on self‐reported information.